Food addiction, in obese patients seeking bariatric surgery, is associated with higher prevalence of current mood and anxiety disorders and past mood disorders. (September 2018) - Benzerouk, Farid; Gierski, Fabien; Ducluzeau, Pierre-Henri; Bourbao-Tournois, Céline; Gaubil-Kaladjian, Isabelle; Bertin, Éric; Kaladjian, Arthur; Ballon, Nicolas; Brunault, Paul
Highlights: The Yale food addiction scale 2.0 is reliable in a population of patients with obesity applying for bariatric surgery. The "food addiction" (FA) phenotype is prevalent in this population. FA is associated with higher prevalence of current mood and anxiety disorders, past mood disorders and higher current suicidality. FA is also associated with higher emotional eating. FA is associated with loss of control over consumption of specific foods that are high in fat, sugar and/or salt, but not of other foods (fruits, vegetables, and grain products). Abstract: The current cross-sectional study investigates the prevalence of the food addiction (FA) phenotype and its association with psychiatric disorders in bariatric surgery candidates. It also investigates the eating behavior characteristics associated with FA and the association between FA and loss of control over specific foods high in sugar, salt and/or fat. We included 128 bariatric surgery candidates and we assessed FA (YFAS 2.0), mood and anxiety disorders, suicidality, eating disorders (current bulimia nervosa and current anorexia nervosa), alcohol and tobacco use disorders (MINI 5.0.0, beck depression inventory, AUDIT, Fagerström Test for Nicotine Dependence) and eating behavior (DEBQ). Prevalence of FA in our sample was 25%. FA was significantly associated with higher prevalence of current mood and anxiety disorders and past mood disorders, higher current suicidality but not with eating disorders and alcohol use disorder. FA was significantly associated with higher emotional eating, and with loss of control over consumption of foods high in fat, sugar and/or salt, but not of fruits, vegetables or grain products. Our results provide arguments for considering psychiatric disorders and suicidality in FA and for considering FA as an addictive disorder in obese patients, with many risk factors in common with other addictions.